A novel monitoring dashboard and hardware implementation simplifying the remote access in industry - KORKMAZ, HAYRİYE (My University, 2023)
In today’s world where technology is developing with a great speed, it is getting harder day by day to adapt or include changes on new technology to the processes in facilities. Insisting on using conventional solutions adopted so far in industrial facilities cause problems to compensate the changing fast consumption needs of today. Adopting recent technologies improves the maintenance and troubleshooting processes of the facilities, accelerates the production and increases the quality of production. In this way, technology based smart systems can provide the devices or machines with the skills required for problem solving and system development in the industry. In this study, a remote monitoring and control application is proposed for a frequency inverter which is widely used and critical device for motor driving in industrial facilities is discussed and a novel internet of things (IoT) based communication gateway is developed. In this way, it is intended to improve the problem solving skills of field personnel by contributing with remote support.
Keywords: Elektrik-Elektronik Mühendisliği; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences; Industrial IoT; Machine-Cloud-Human Interaction; Remote Monitoring and Control; Frequency Inverters; Smart Machines; Smart Factories